Longitudinal Analysis of Biochemical, Imaging, and Adenoma Size Changes in Primary Hyperparathyroidism - Aycicek, Bercem; Tuna, Mazhar Muslum; Engin, Ismail; Canpolat, Asena Gokcay; Yigit, Ekin; Firat, Sevde Nur; Elbuken, Gulsah (Georg Thieme Verlag Kg, 2026)
Background Primary hyperparathyroidism (PHPT) is a prevalent endocrine disorder characterized by disrupted calcium-phosphorus homeostasis. Accurate biochemical assessment, including albumin-corrected calcium, and preoperative localization of parathyroid adenomas are essential for optimal management. This study aimed to evaluate temporal changes in imaging detectability, biochemical markers, and adenoma size, and to assess novel biochemical indices in patients with asymptomatic PHPT (aPHPT). Methods In this multicenter retrospective study, 416 aPHPT patients underwent clinical, biochemical, and radiological evaluation at three time points. Biochemical parameters included albumin-corrected calcium, phosphorus, parathyroid hormone (PTH), 25-hydroxyvitamin D, alkaline phosphatase (ALP), and 24-hour urinary calcium. Novel indices-calcium/phosphorus (Ca/P), PTH/phosphorus (PTH/P), and calcium & times;chloride/phosphorus (Ca & times;Cl/P)-were calculated to evaluate diagnostic and predictive value. Imaging included high-resolution neck ultrasonography, 99mTc-sestamibi SPECT/CT, and four-dimensional CT to assess adenoma detectability and size changes. Statistical analyses included repeated-measures ANOVA or Friedman tests for temporal comparisons, correlation analyses, logistic regression for predictors of adenoma detection, and ROC curves to evaluate diagnostic accuracy. A p-value<0.05 was considered significant. Results Among 416 patients (87% female), ultrasound-detected adenomas decreased over time due to surgery of clearly visible lesions. CT and SPECT/CT initially improved localization, with later decline in CT but continued gains in SPECT/CT. Adenoma size increased, and the PTH/phosphorus ratio changed significantly. Baseline albumin-corrected calcium, phosphorus, and adenoma size predicted radiological detectability, with ROC AUCs of 0.78 for adenoma size and 0.72 for phosphorus. Surgically treated patients exhibited more pronounced biochemical abnormalities and superior CT-based localization. Conclusion Following imaging and biochemical assessments, including albumin-corrected calcium, improve detection, monitoring, and management of aPHPT. Novel indices such as PTH/phosphorus and Ca/P ratios provide practical, low-cost tools for early disease identification and risk stratification. Integrating dynamic biochemical markers with imaging supports individualized, evidence-based clinical decision-making.
Keywords: Primary hyperparathyroidism; parathyroid adenoma; biochemical indices; imaging modalities; Ca/P ratio; PTH/phosphorus ratio